Staying SHARP in times of crisis – The impact of COVID-19 on anaesthesiology residency - Denise Yan Yin Lim; Von Vee Ng; Zihui Tan; Darren LK Koh (Proceedings of Singapore Healthcare, 2021)
The COVID-19 pandemic is an unprecedented crisis that has taken the world by storm, and it has taken an especially immense toll on the healthcare sector. Although much effort has been made to make changes in key areas such as clinical practice, national policy and research, we believe that it is just as important to evaluate the impact of the crisis on postgraduate medical training. To this end, we would like to share our experience within an anaesthesiology residency programme in Singapore, the SingHealth Anaesthesiology Residency Programme, which we hope will benefit other training programmes and anyone involved in postgraduate medical education as a whole. Key challenges identified include restrictions on teaching events, difficulties in completing core posting requirements, changes in clinical workload, postponement of examinations, exposure risk (particularly in relation to aerosol-generating procedures) and psychological burden. Strategies that have been implemented to tackle these challenges are also described, including the use of online platforms, modifications to posting and promotion requirements, manpower adjustments, provision of protective equipment and training in infectious disease protocols. Ultimately, we believe that a supportive work environment is essential to ensure the wellbeing of residents in times of crisis.